Uji Toksisiti Asam Α-Linolenik Rumput Laut Ulva sp. Terhadap Chattonella marina Dan Heterosigma akashiwo [Toxicity Assay Of Α-Linolenic Acid From Ulva sp. Seaweed On Chattonella marina And Heterosigma akashiwo] - Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract The higher toxicity of α-linolenic acid from Ulva sp. seaweed showed the high algicidal activity against Chattonella marina and Heterosigma akashiwo. Among six species tested, C. marina and H. akashiwo was the most susceptible to this fatty acid, whereas LC50 of α-linolenic acid was estimated to be 3.22 and 0.58 µg/mL, respectively. Furthermore, α-linolenic acid also showed algicidal activity against Alexandrium tamarense and A. taylori. It is suggested that α-linolenic acid is useful mitigation agents to Harmful Algal Bloom effect, especially on Chattonella marina and Heterosigma akashiwo.